bni: A PDDL to C compiler with integrated REPL for interactive testing - Ribeiro, Bruno Campos; Penha, Igor e Silva; Ribas, Bruno Cesar (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2025)
This paper presents the implementation of a modular parser and an interactive REPL PDDL, entirely developed in the C programming language. The proposed solution enables the translation of PDDL domain and problem specifications into efficient, manipulable C data structures, fostering transparency, performance, and portability. Complementing the parser, the integrated REPL facilitates incremental testing and interactive debugging of planning domains and problem instances, supporting a cycle of real-time action validation and state exploration. The system also incorporates an integrated validation functionality. This feature enables both incremental and post hoc verification of action sequences and complete plans, ensuring that they adhere to the defined domain and problem specifications. The validate capability of the tool allows users to detect logical inconsistencies and confirm goal achievement efficiently, even in large-scale instances. Compared to established tools such as VAL, the proposed solution offers improved flexibility and performance for plan validation, particularly in scenarios involving extensive and complex plans. This work represents a novel contribution to the field of automated planning, bridging the gap between high-level modelling languages and low-level systems programming.